2019
DOI: 10.30812/varian.v3i1.436
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Faktor-Faktor yang Mempengaruhi Tingkat Kemiskinan Kabupaten dan Kota Provinsi Sulawesi Selatan

Abstract: The purpose of this study is to analyze the factors that influence the poverty rates in the Regencies and Cities of South Sulawesi Province. This type of research is applied research with secondary quantitative data. The data used in this study are secondary data obtained by the Central Statistics Agency (BPS) including population data; PDRB per capita; AMH, AHH, and the poverty rates of Regencies and Cities in South Sulawesi in 2019. Based on the results of the study it can be concluded that the population, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
1
1
0
2
Order By: Relevance
“…Real assets have higher risks than monetary assets, especially in conditions of economic and political uncertainty. Monetary assets have higher liquidity than real assets, so they can be easily is in line with research conducted by (Ahmad Ridha et al, 2021;Arwin et al, 2019;Folarin & Asongu, 2023;Hayati, 2015;Nurmetri & Adnan, 2022;Nursiba, 2015;Polontalo et al, 2018;Setiadi, 2013;Wang et al, 2014;Widodo A, 2015;Yulimar, 2015) One of the factors influencing M2 money demand is interest rates. Interest rates have a negative correlation with M2 money demand due to two effects: the substitution effect and the income effect.…”
Section: Discussionsupporting
confidence: 76%
“…Real assets have higher risks than monetary assets, especially in conditions of economic and political uncertainty. Monetary assets have higher liquidity than real assets, so they can be easily is in line with research conducted by (Ahmad Ridha et al, 2021;Arwin et al, 2019;Folarin & Asongu, 2023;Hayati, 2015;Nurmetri & Adnan, 2022;Nursiba, 2015;Polontalo et al, 2018;Setiadi, 2013;Wang et al, 2014;Widodo A, 2015;Yulimar, 2015) One of the factors influencing M2 money demand is interest rates. Interest rates have a negative correlation with M2 money demand due to two effects: the substitution effect and the income effect.…”
Section: Discussionsupporting
confidence: 76%
“…Study (Harianja et al, 2018) use The Average Length of Schooling is a representation of the level of education showed that negatively affects on poverty, but Life Expectancy has no effect on poverty in Papua. Result (Suryati & Syukri, 2019) partially Life Expectancy has no effect on the poverty rate in South Sulawesi.…”
Section: Introductionmentioning
confidence: 88%
“…Terdapat beberapa paramater dalam SNA untuk mengukur sentralitas aktor dalam hubungannya pada suatu jaringan kelompok antara lain melalui degree centrality, closeness centrality, dan betweenness centrality [11]. Dalam analisis jaringan sosial (SNA), input data yang direpresentasikan adalah Faktor Kunci Pengentasan Kemiskinan -Pertumbuhan penduduk yang tinggi [1] Penyediaan basis data terpadu kemiskinan -Terbentuknya kelas-kelas ekonomi dalam Masyarakat [17] -Perubahan demografis [18] -Rendahnya pendapatan dan aset untuk memenuhi kebutuhan dasar [19] Pengurangan beban pengeluaran masyarakat -Kualitas sumber daya manusia dan penguasaan teknologi yang rendah [17][20] -Ratarata lama sekolah [20] -Upah Minimum Regional [20] -Kurangnya lapangan kerja, ketiadaan kesempatan [1] [18] Peningkatan pendapatan masyarakat -Kualitas angkatan kerja yang rendah, keterbatasan akses permodalan [1] [17] -Perubahan pasar tenaga kerja [18] -Terkucilkan, akses yang terbatas, dan keterbatasan sumber daya alam [1] [17] Penurunan kantong-kantong kemiskinan -Adanya disparitas karena munculnya pemusatan perkembangan di perkotaan [17] -Ketimpangan sosial [20] -Rentan Terhadap Guncangan Ekonomi Stabilisasi Harga -Inflasi akan meningkatkan biaya produksi yang menimbulkan kenaikan harga barang dan jasa, menyebabkan daya beli masyarakat menurun [10] [18] -Tingkat inflasi [20] dalam bentuk matriks. Hubungan antar aktor dalam matriks digambarkan dengan nilai 1 dan 0, angka 1 melambangkan adanya relasi sedangkan angka 0 melambangkan tidak adanya relasi di dalam jaringan.…”
Section: F Kolaborasi Stakeholderunclassified